Analysis of intrapulpary temperature variation during the operative and restorative phase in human molars (Research, Society and Development, 2023)
The aim of this study was to analyze the intrapulpal temperature variation during the operative and restorative phase in human molars. This study was approved by the Research Ethics Committee, registration CAAE 43677521.6.0000.5237 and 24 samples were made from human molars divided into 2 groups, group 1 (n = 12) restored with Bulk Fill composite resin in a single increment and group 2 (n = 12) restored with conventional composite resin in two increments. The temperature was monitored and recorded with a Lutron Tm-902C digital thermostat device during preparation, adhesive system application and restoration. The mean temperature variation in ºC for cavity preparation was -2.07 ± 0.89, application of the adhesive system was 1.12 ± 0.65, restoration with Bulk Fill resin was 2.73 ± 0.72 and restoration with conventional resin was 1.94 ± 0.35. Thus, in the operative phase there was a decrease in temperature in both groups and in the restorative phase the Bulk Fill resin presented a higher temperature compared to conventional resin.